Strategi Komunikasi Pemerintah dalam Implementasi Program Makan Bergizi Gratis (MBG) : Studi Kasus SMKN 1 Jogonalan - Awi Pujiyanto; Manap Solihat (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2026)
The Free Nutritious Meal Program (MBG) is implemented as a government effort to improve nutrition, health, and reduce stunting rates in Indonesia. This program has been running for approximately ten months, but during its implementation, several cases of poisoning were found in several areas that raised some concerns for the community, especially for students and parents who received MBG. This study focuses on the communication process theory according to Effendy including communicators, messages, channels, communicants, and effects. This study uses a descriptive qualitative approach in the form of specific interviews with the Nutrition Fulfillment Service Unit (SPPG) Lumbung Karya Nusantara Plawikan, teachers, and students at SMKN 1 Jogonalan, Klaten Regency. The author used purposive sampling in selecting key informants who were considered to have the most knowledge and in-depth information about MBG, including the head of SPPG, six students who received MBG, and the teacher in charge of MBG, then the information was processed with thematic analysis. The research results found that there are still several aspects of communication that have not been implemented, such as the school as the communicator has not delivered an official message to students and parents and social media as a channel to provide information on the MBG program to students and parents whose information validity is considered lacking, thus raising concerns about the MBG program. Several of these findings indicate the need for increased socialization of the MBG program that is valid, a variety of digital and conventional content and adjustments to further communication strategies for the government or related institutions. This research emphasizes the importance of transparent, fast, and empathy-oriented public communication, especially social policies that touch people's lives. The results of this study are expected to be a consideration for the government and related institutions in developing more effective communication programs, especially the MBG program.